A Demand for Narrative: Reading Sabahattin Ali's Novel Kuyucaklı Yusuf as a Quest for Identity - Murat Baran Akkuş (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
Sabahattin Ali's first novel, Kuyucaklı Yusuf, published in 1937, is a historically significant text within Turkish literature; it is the first realistic novel about Anatolian life and is a critique of the social system. However, the novel remained incomplete due to Ali's murder in 1948 amid a rising tide of authoritarianism and nationalism that he consistently critiqued. This study examines the novel's demand for narrative identity in the context of its creator's untimely death. The study reveals three obstacles: “the silent language of victimhood,” the extreme experience of loneliness, and the finality of the author's death, all of which function as barriers to realizing personal narratives. This exploration is also an attempt at an act of sepulcher, as defined by Paul Ricoeur, which means mourning the author's death by revising the incompleteness of Yusuf's identity. Ali’s novel is an example of an ethical mode of authoring that requires giving up authoritative control over real or fictional life stories. Acknowledging the existence of untold stories alongside the potential for new narratives attests to the power of storytelling through the vulnerability of a life story.